Differential Subordination Results for Analytic Functions in the Upper Half-Plane. (25th February 2014) - Tang, Huo; Aouf, M. K.; Deng, Guan-Tie; Li, Shu-Hai
Abstract : There are many articles in the literature dealing with differential subordination problems for analytic functions in the unit disk, and only a few articles deal with the above problems in the upper half-plane. In this paper, we aim to derive several differential subordination results for analytic functions in the upper half-plane by investigating certain suitable classes of admissible functions. Some useful consequences of our main results are also pointed out.